Need for modernizing financial institutions - Heiko Körner (Intereconomics, 1975)
As the flow of financial aid from the industrial countries may be expected to shrink rapidly as a consequence of their economic difficulties, the developing countries will have to find out possibilities of using their own financial resources more effectively. In this connection the task of modernizing their financial institutions should not be neglected.
Keywords: 330; Financing